2010
DOI: 10.1111/j.1949-3606.2010.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Community of Practice in the Kuwaiti Medical Sector: An Exploratory Study

Abstract: Community of Practice (CoP) is a relatively new concept in the Middle East and North Africa. The concept has been used for a number of years in the business sector; however, the use of CoPs in the health sector has not been as widespread. The aim of this study is to provide insights into the status of CoPs in the health sector and the knowledge sharing practices that take place among members of such CoPs in Kuwait. Ninety‐eight questionnaires were distributed among medical practitioners. Results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Fullwood et al [75] found that motivators for educators in United Kingdom, sharing knowledge are one of the extrinsic motivations for promotion. Nevertheless, from a survey involving medical professionals of Kuwait, most respondents stated that they haven't receive monetary rewards for knowledge sharing and their major motivation to share was a wish to help and learn from others [76]. These finding recommends that other features for example industry or cultural context may mediate the relationship among knowledge and rewards sharing.…”
Section: ) Motivators (Mo)mentioning
confidence: 99%
“…Fullwood et al [75] found that motivators for educators in United Kingdom, sharing knowledge are one of the extrinsic motivations for promotion. Nevertheless, from a survey involving medical professionals of Kuwait, most respondents stated that they haven't receive monetary rewards for knowledge sharing and their major motivation to share was a wish to help and learn from others [76]. These finding recommends that other features for example industry or cultural context may mediate the relationship among knowledge and rewards sharing.…”
Section: ) Motivators (Mo)mentioning
confidence: 99%
“…However, CoPs are relatively new in the Middle East and North Africa (MENA) area (Idris, 2007). Marouf and Al-Attabi (2010) conducted a study in the health sector in Kuwait. They claim that the CoP is a relatively new approach in MENA.…”
Section: Communities Of Practice In Western and Non-western Contextsmentioning
confidence: 99%
“…Also, tendency to learn and help others was found to be one of the main motivators for medical professionals in Kuwait to share knowledge. Those professionals stated that there were no rewards to receive for sharing as reported by (Marouf and Al-Attabi, 2010). These findings provide evidence of the role played by the context of culture or industry in moderating the relationship between rewards and knowledge sharing.…”
Section: Knowledge Management Sharingmentioning
confidence: 73%